CFSP RESTRICTIVE MEASURES IN THE CJEU’S JURISPRUDENCE: BETWEEN HUMAN RIGHTS AND EU AUTONOMY - Tošić, Jovana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2026)
This article analyses how the Court of Justice of the European Union (CJEU) reviews restrictive measures adopted under the Common Foreign and Security Policy (CFSP) and, in doing so, balances foreign-policy effectiveness with fundamental rights. Using doctrinal analysis of the Treaties and key judgments, it shows that the Court has developed a predominantly procedural model of review while progressively widening the jurisdictional gateways for judicial control. The CJEU applies demanding scrutiny to reasons-giving, the right to be heard and the evidentiary basis of listings, while remaining deferential as to the Council’s complex political assessments. The article argues that this calibration enhances legality and transparency but may under-protect rights where listings are long-lasting and generate effects comparable to punitive measures. It proposes a more structured proportionality inquiry, clearer evidentiary thresholds and improved handling of confidential material through more rigorous periodic review.
Keywords: Human rights, restrictive measures, CFSP, CJEU, judicial review.; људска права, рестриктивне мере, Заједничка спољна и безбедносна политика, Суд правде ЕУ, судска контрола.